Providing electronic internet evidence in Russian notarial and judicial practice for civil law disputes (Revista de Investigaciones Universidad del Quindío, 2022)
The current study is mainly devoted to the analysis of the current Russian legislation and the emerging notarial and judicial practice in the field of providing electronic evidence, the features and problems of procedures for their notarization, the relevance and admissibility of electronic evidence in civil law disputes in courts of general jurisdiction and arbitration courts as a factor in stabilizing civil law turnover carried out in information and communication formats (digital economy). Moreover, the study considers the problems of legal recording electronic traces while noting the most significant aspects of this recording of the evidence and formulating recommendations for notaries and parties to judicial disputes. To that aim, a range of general scientific methods, including observational, descriptive, and qualitative approaches, are used. Based on the results, the Russian regulatory system must have mechanisms for fixing traces of such civil activity to use them as evidence in civil and arbitration disputes.
Keywords: securing evidence; digital traces; digital documents; notary public; notarial services